Time-variant travel time distributions and reliability metrics and their utility in reliability assessments - Alvarez, Patricio; Hadi, Mohammed (Congreso Chileno de Ingeniería de Transporte, 2013)
There are metrics of reliability that have been recommended. Here we investigate the variation of travel time distributions by time of day at fine temporal aggregation levels, the sensitivity of reliability metrics to these variations, the effect of the aggregation on the calculated metrics, and the amount of data required to estimate stable values of the reliability metrics. The results show that the parameters of travel time distributions vary among periods reflecting the effects of the traffic congestion, traffic flow dynamics, and the contribution of non-recurrent factors such as incidents to the unreliability of travel time on the investigated facility.